Requirement, Dietary Sources, and Efficiency of Absorption of Major Minerals by Farm Animals: From an Educational Perspective - Janet Chinwe Olowoyeye (Universitas Pendidikan Indonesia, 2022)
The necessity of the inclusion of major minerals in the diet of farm animals cannot be overemphasized. The production of the much-needed animal protein can be severely hampered when unrecognized conditions of deficiency, oversupply, or in-balance of minerals exist and interfere with the intensification of livestock production. Here, the purpose of this study was to explain this matter based on an educational perspective. This paper is a literature survey. This paper is important to make farmers understand the requirement, dietary sources, and efficiency of absorption of major minerals by farm animals. For the best production of any livestock, the requirement for each mineral must be known. Lack of adequate minerals in the diet of farm animals is associated with late maturity, prolonged breeding period, reproductive disorders, poor growth, anemia, and a high rate of mortality.